2011
DOI: 10.1038/nchem.1029
|View full text |Cite
|
Sign up to set email alerts
|

Directed long-range molecular migration energized by surface reaction

Abstract: The recoil of adsorbates away (desorption) and towards (reaction) surfaces is well known. Here, we describe the long-range recoil of adsorbates in the plane of a surface, and accordingly the novel phenomenon of reactions occurring at a substantial distance from the originating event. Three thermal and three electron-induced surface reactions are shown by scanning tunnelling microscopy to propel their physisorbed ethylenic products across the rough surface of Si(100) over a distance of up to 200 Å before an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 43 publications
8
29
0
Order By: Relevance
“…This finding suggests that, besides playing a key role in CVD activation, molecular rolling may be a more general phenomenon characterizing molecule‐surface interactions. Support to this hypothesis is also provided by recent studies , where small alkene molecules, stimulated either by exotermic surface reactions or by STM electron beams on Si(100), have evidenced a similar behavior in the 298–443 K range.…”
Section: Resultssupporting
confidence: 56%
“…This finding suggests that, besides playing a key role in CVD activation, molecular rolling may be a more general phenomenon characterizing molecule‐surface interactions. Support to this hypothesis is also provided by recent studies , where small alkene molecules, stimulated either by exotermic surface reactions or by STM electron beams on Si(100), have evidenced a similar behavior in the 298–443 K range.…”
Section: Resultssupporting
confidence: 56%
“…The competition between the e-h pairs and phonon channels governs the relaxation dynamics of the transient hot species, and thus it plays a decisive role in the system reactivity properties. The reason is that it rules the traveled length and relaxation time of a hot atom or molecule on the surface and, consequently, the probability to undergo a recombination reaction with another adsorbate [18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…The competition between the e-h pairs and phonon channels governs the relaxation dynamics of the transient hot species, and thus it plays a decisive role in the system reactivity properties. The reason is that it rules the traveled length and relaxation time of a hot atom or molecule on the surface and, consequently, the probability to undergo a recombination reaction with another adsorbate [18][19][20][21][22][23].Recent ab initio molecular dynamics (AIMD) simulations with electronic friction (AIMDEF) have shown that e-h pair excitations are the dominant relaxation mechanism for hot H atoms on Pd(100) that originate from the dissociative adsorption of H 2 [16]. More particularly, this channel dissipates energy at a five times faster rate than the phonon channel [10].…”
mentioning
confidence: 99%
“…An accurate description of quantum dynamics is needed in many areas of physics and related disciplines, including photovoltaic and photocatalytic applications [1][2][3], lightoperated nanoscale materials [4,5] and molecular electronics [6][7][8][9]. The large number of quantum, semiclassical, and quantum-classical techniques of varying complexity have been developed over the last few decades [10][11][12][13][14][15] and successfully applied to study nonequilibrium processes such as electron-phonon relaxation [1,[16][17][18], charge and energy transfer [19,20], and photoinduced atomistic rearrangements [21,22].…”
mentioning
confidence: 99%